2019
DOI: 10.17921/2447-8938.2019v21n1p58-64
|View full text |Cite
|
Sign up to set email alerts
|

Dentist’s Behavior Regarding Children and Adolescents Maltreatment

Abstract: Child abuse is a serious violation of the child’s basic rights and the precocious diagnosis of maltreatment cases and early intervention are important for the protection of the involved individuals. Most of the lesions involve the mouth, craniofacial regions, and neck. Therefore, dentists are in an exceptionally favorable position to recognize child abuse. Thus, the aim of the present study, through an integrative review, to guide dentists in the identification and report of children and adolescents’ maltreatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
5

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 8 publications
0
5
0
5
Order By: Relevance
“…Most of the selected articles address child abuse in a general manner 24,26,[29][30][31][32][34][35][36][39][40][41][42][43][44][45][46][47] without specifying the type of violence. In the studies that reported type of violence, the most common types were physical 27,28,37 and sexual 25,33,38 violence.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Most of the selected articles address child abuse in a general manner 24,26,[29][30][31][32][34][35][36][39][40][41][42][43][44][45][46][47] without specifying the type of violence. In the studies that reported type of violence, the most common types were physical 27,28,37 and sexual 25,33,38 violence.…”
Section: Discussionmentioning
confidence: 99%
“…The studies encompassed the areas of education, health, public security, social services, and child protection networks. The area of health accounted for the largest number of studies, with 12 articles 24,[27][28][29][30][31]39,[41][42][43][44][45] plus two articles involving both health and social services 32,35 . The areas of education 36 and public security 38 accounted only for 1 article each.…”
Section: Characterization Of the Articlesmentioning
confidence: 99%
See 3 more Smart Citations